2020
DOI: 10.3390/molecules25010214
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Protects PC12 Cells against Homocysteine- and Glutamate-Induced Neurotoxicity

Abstract: Memory impairment has been shown to be associated with glutamate (Glu) excitotoxicity, homocysteine (Hcy) accumulation, and oxidative stress. We hypothesize that Glu and Hcy could damage neuronal cells, while astaxanthin (ATX) could be beneficial to alleviate the adverse effects. Using PC12 cell model, we showed that Glu and Hcy provoked a huge amount of reactive oxygen species (ROS) production, causing mitochondrial damage at EC50 20 and 10 mm, respectively. The mechanisms of action include: (1) increasing ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Correspondingly, we also found significant loss in neuronal survivability on glutamate addition. Interestingly, similar to the earlier observations [ 36 , 46 ], we observed high neuronal survivability upon glutamate exposure in AST preincubated cultures. In neurons, the glutamate toxicity is majorly due to the excessive intracellular calcium overload, which involves a rapid primary calcium influx and an irreversible SSCR [ 18 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Correspondingly, we also found significant loss in neuronal survivability on glutamate addition. Interestingly, similar to the earlier observations [ 36 , 46 ], we observed high neuronal survivability upon glutamate exposure in AST preincubated cultures. In neurons, the glutamate toxicity is majorly due to the excessive intracellular calcium overload, which involves a rapid primary calcium influx and an irreversible SSCR [ 18 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…The SSCR is associate with the loss of mitochondrial function, which in turn depends on the primary influx of calcium into the neuron from the extracellular space [ 6 ]. Earlier reports by fluorometric analysis have suggested that AST attenuates the [Ca 2+ ]i response in PC12 and SH-SY5Y cells upon glutamate application [ 36 , 46 ], and in hippocampal neurons upon NMDA application [ 27 , 37 ]. However, these studies have not demonstrated AST-mediated inhibition of both the primary Ca 2+ influx as well as the SSCR upon ionotropic glutamate receptor agonists activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These responses were explained by Chang et al. (2020), who suggested that glutamate provokes a significant amount of ROS production. ROS induces inflammation and causes the release of multiple pro‐inflammatory cytokines, including TNF‐α and IL‐6, which play a role in the inflammatory hepatic response and therefore cause liver injury (Bryan et al., 2012).…”
Section: Discussionmentioning
confidence: 91%
“…A remarkable property of ASX is that, unlike many other natural antioxidants, it readily crosses the blood-brain barrier; due to this property, ASX has been used successfully in rodents to reverse both ischemia-reperfusion-induced brain damage [5] and cognitive impairment [6,7]. In neuron-like HT22 cells [7], PC12 cells [8] or SH-SY5Y cells [9][10][11] ASX suppresses the excitotoxic responses induced by glutamate, 6-hydroxydopamine (6-OHDA), 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) or acetaldehyde. Although the neuroprotective effects of ASX might involve decreasing oxidative stress and improving mitochondrial integrity [12], whether ASX induces adaptive responses such as changes in redox-sensitive cellular signaling processes-including calcium (Ca 2+ )-dependent signaling pathways and reactive oxygen species (ROS) generation remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%